Review of Why Horror Seduces - Molnár, András (AMERICANA E-journal of American Studies in Hungary, 2018)
Why Horror Seduces Mathias Clasen Oxford: Oxford University Press, 2017 190 pages ISBN: 978-0-19-066651-4